2010
DOI: 10.1051/0004-6361/200913101
|View full text |Cite
|
Sign up to set email alerts
|

Chromospheric magnetic reconnection caused by photospheric flux emergence: implications for jet-like events formation

Abstract: Magnetic reconnection in the low atmosphere, e.g. chromosphere, is investigated in various physical environments. Its implications for the origination of explosive events (small-scale jets) are discussed. A 2.5-dimensional resistive magnetohydrodynamic (MHD) model in Cartesian coordinates is used. It is found that the temperature and velocity of the outflow jets as a result of magnetic reconnection are strongly dependent on the physical environments, e.g. the magnitude of the magnetic field strength and the pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 31 publications
(40 reference statements)
2
25
0
Order By: Relevance
“…For example, the numerical results in the paper by Chen et al (2001), Archontis & Hood (2009) and Xu et al (2011) show that the temperature enhancement for EBs is around several thousands Kelvin and the lifetime is around several minutes, which are similar as the observation results of EBs. By setting suitable initial magnetic fields and plasma density, the numerical simulations can lead to the formation of chromosphere jets which have similar topology structures as from the observations, the up-flow speeds from the simulations can be in the range around 10 − 130 km −1 (Ding et al 2010Yang et al 2013), which are the same as the speeds of the observed chromosphere jets. On the other hand, some numerical simulations focus more on the physical mechanisms of magnetic reconnection in solar chromosphere, the partially ionized effects including ambipolar diffusion and recombination have been studied detailedly (e.g., Leake et al 2012;Murphy & Lukin 2015;Singh et al 2015).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…For example, the numerical results in the paper by Chen et al (2001), Archontis & Hood (2009) and Xu et al (2011) show that the temperature enhancement for EBs is around several thousands Kelvin and the lifetime is around several minutes, which are similar as the observation results of EBs. By setting suitable initial magnetic fields and plasma density, the numerical simulations can lead to the formation of chromosphere jets which have similar topology structures as from the observations, the up-flow speeds from the simulations can be in the range around 10 − 130 km −1 (Ding et al 2010Yang et al 2013), which are the same as the speeds of the observed chromosphere jets. On the other hand, some numerical simulations focus more on the physical mechanisms of magnetic reconnection in solar chromosphere, the partially ionized effects including ambipolar diffusion and recombination have been studied detailedly (e.g., Leake et al 2012;Murphy & Lukin 2015;Singh et al 2015).…”
Section: Introductionmentioning
confidence: 67%
“…Most of the previous numerical simulations which focus on the formations of EBs (e.g., Chen et al 2001;Isobe et al 2007;Archontis & Hood 2009), chromosphere jets (e.g., Ding et al 2010Ding et al , 2011Yang et al 2013) and micro-flares (e.g., Jiang et al 2012;Archontis & Hansteen 2014) are studied based on the single fluid MHD equations with an assumed anomalous resistivity. The topology structures and many characteristics in these numerical simulations can match well with the observation results.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ding et al (2010) used a 2.5-dimensional resistive MHD model in Cartesian coordinates to investigate magnetic reconnection in the low atmosphere, e.g. chromosphere, discussing the implications for jet features at transition-region temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that faster and hotter outflows could be obtained if a physical environment with lower mass density was considered, however, the highest temperature of the plasma heated by magnetic reconnection is only 5 × 10 5 K in their study. Here, we expand the work of Ding et al (2010) varying the electron density and field strength as applied to a larger range of jet features, including fibrils, spicules, chromospheric jets and transition region jets. This work uses a larger grid model (see later) than the previous study.…”
Section: Introductionmentioning
confidence: 99%
“…Recent examples of numerical simulations of explosive events in this scenario can be found in Ding et al (2010), Heggland et al (2009), Litvinenko & Chae (2009), and Chen & Priest (2006).…”
Section: Introductionmentioning
confidence: 99%